Reconstitution of cytomegalovirus-specific T-cell response in allogeneic hematopoietic stem cell recipients: the contribution of six frequently recognized, virus-encoded ORFs - Němečková, Šárka; Kryštofová, Jitka; Babiarová, Katarína; Hainz, Petr; Musil, Jan; Šroller, Vojtěch; Malý, Marek; Marková, Markéta (Transplant infectious disease, 2016)
BACKGROUND: The reactivation of human cytomegalovirus (HCMV) in immunosuppressed patients is associated with significant morbidity. Testing HCMV-specific T-cell responses can help determine which patients are at high risk of HCMV disease. We optimized selection of HCMV antigens for detection of T-cell response of patients after allogeneic hematopoietic stem cell transplantation (HSCT) with the aim of identifying patients with insufficient control of HCMV reactivation. METHODS: T-cell immune response to HCMV was monitored in 30 patients during the first year after HSCT. The HSCT recipients were classified according to their anti-HCMV T-cell response and the presence of HCMV DNA in the blood. RESULTS: We observed an inverse relationship between the magnitude of HCMV-specific T-cell responses against CMV lysate, phosphoprotein (pp) 65, immediate early-1 (IE-1), UL36, and UL55, but not to US3 and US29 detected by interferon-gamma (IFNγ)- ELISPOT and the level of HCMV DNA in the blood of patients during the 30 days following sampling. The study has revealed that patients who received a graft from a seronegative donor have a lower T-cell response against HCMV and increased probability of HCMV reactivation in comparison to the patients who had received their graft from a seropositive donor. CONCLUSION: The individual peptide pools and native HCMV antigens were useful for monitoring the time course of the anti-HCMV response by IFNγ-ELISPOT, which proved to have a prognostic value. Besides widely employed peptide pools of pp65 and IE-1, the use of antigens UL36 and UL55, but not US3 or US29, increased sensitivity of the test.
Keywords: Female; interferon gama; Cytomegalovirus Infections; lidé středního věku; mužské pohlaví; Antiviral Agents; virové proteiny; Humans; antivirové látky; Interferon-gamma; fosfoproteiny; transplantace hematopoetických kmenových buněk; Phosphoproteins; antigeny virové; cytomegalovirové infekce; Hematopoietic Stem Cell Transplantation; lidé; Cytomegalovirus; Middle Aged; ELISPOT; Immunocompromised Host; CD8-pozitivní T-lymfocyty; ženské pohlaví; CD8-Positive T-Lymphocytes; Enzyme-Linked Immunospot Assay; Male; imunokompromitovaný pacient; Antigens, Viral; Viral Proteins